A Formal Framework for Representing Mechanisms?. Issue 1 (January 2014) - Gebharter, Alexander
Abstract : In this article I tackle the question of how the hierarchical order of mechanisms can be represented within a causal graph framework. I illustrate an answer to this question proposed by Casini, Illari, Russo, and Williamson and provide an example that their formalism does not support two important features of nested mechanisms: (i) a mechanism's submechanisms are typically causally interacting with other parts of said mechanism, and (ii) intervening in some of a mechanism's parts should have some influence on the phenomena the mechanism brings about. Finally, I sketch an alternative approach taking (i) and (ii) into account.